Medico-legal profile of cases referred for age determination to a Government tertiary care hospital in Mumbai, Maharashtra: A three-year retrospective study - Bhore, D V; Chavan, G S; Nanandkar , S D (Journal of Indian Academy of Forensic Medicine, 2019)
Estimation of age of living individual is of great importance and is necessary for the purpose of administration of justice. Age estimation is important in both civil and criminal cases. Determination of age is playing a key role in cases where exact age is not known or proof of birth is not available, because many births take place at home or in a rural area where lack of maternity hospital is the issue and documentation of such births are not up to date. In medico-legal cases, the age of an individual is determined by a forensic practitioner on requisition from a police officer or magistrate or session’s judge or juvenile justice board. Age of individual is determined by radiological assessment, dental and physical examination. Total of 305 cases of age determination were studied. Out of which 211(69.18%) were females and 94(30.82%) were males. Female victim cases were 210(68.85%) and male accused cases were 81(26.65%). Most cases i.e. 162(53.12%) belongs to the age group between 15 years to 18 years. 281(92.13%) cases belong to the urban area and 248(81.31%) cases were unmarried. Cases of victims registered under 376 IPC were 80, 363, 366 IPC were 87, 294 IPC were 7, POCSO act were 90, 377 IPC were 8, 354 IPC were 16 and under PITAact were 58. Cases of accused registered under 376 IPC were 30, POCSO act were 43, 377 IPC were 12, 354 IPC were 9, 363,366 IPC were 21, 302 IPC were 8 and under 379 IPC were 6. Most of the female victims belong to the age group 15 to 18 years. Epiphyseal fusion around the elbow joint, wrist joint & pelvis found to be earlier in females than males.